PENINGKATAN SISTEM PENGELOLAAN KEUANGAN DAN PEMASARAN DIGITAL PADA UMKM CHALODO SIBALI RESOE - Zikra Supri; Sahrir Sahrir; Rahmad Solling Hamid; Sultan Sultan; Riyanti Riyanti (Jurnal Abdi Insani, 2023)
Digital transformation is one of the main factors in the development and sustainability of Micro, Small and Medium Enterprises (MSMEs). The existence of Law (UU) No. 11 of 2020 concerning Job Creation is a form of government support that is also related to MSME digitization efforts. However, this effort is still not fully carried out by MSMEs on the grounds that they still have obstacles or problems in its implementation. . The partner in this service is the Chalodo Sibali Resoe MSME which produces processed chocolate products. The urgency of the implementation of this service is related to solving the problems faced by partners, including the need for financial system applications, increasing knowledge and taxation capabilities and digital marketing. The purpose of community service activities in general is to provide solutions to partners related to the problems faced in the form of programs and outputs that can later be utilized by the community / partners. The solutions provided include making financial management system applications and implementing socialization and training in taxation and digital marketing. Through this service activity, partners can increase knowledge about taxation and digital marketing, as well as the availability of simple financial reports that are in accordance with the activities and types of business of the partners.